Dinamika Sikap Warga atas Program CSR Bank Sampah Gunung Anyar Surabaya - Nugraheni, Yuli; Widyaningrum, Anastasia Yuni (Faculty of Communications Science, Dr. Soetomo University, 2019)
The research was carried out with the aim of looking at citizens' acceptance of the CSR program implemented by PT PLN. The theory used is the theory of community relations, the theory of corporate social responsibility and attitude theory. Recipient and not the recipient of the program. The results showed that the characteristics of the majority of respondents obtained were as follows: female, aged 41-60 years, having a job as a housewife, education last graduating from elementary school and equivalent. The status of the population is the original citizen and recipient of CSR assistance programs. recipients of CSR programs and attitudes of citizens not recipients of CSR programs are positive. However, the figures obtained by the attitude of residents who are not program recipients are lower than the attitudes of recipients of CSR programs.